2022
DOI: 10.3390/pr10081565
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficient Anionic Dyes Removal from Water by Cationic Polymer Brush Functionalized Magnetic Mesoporous Silica Nanoparticles

Abstract: High efficiency removal of methyl orange (MO) and bromothymol blue (BT) dyes from contaminated water has been reported using magnetic mesoporous nanoparticles modified with cationic polymer brush (poly(2-methacryloyloxy)ethyl] trimethylammonium chloride solution) (Fe3O4-MSNs-PMETAC). Atom transfer radical polymerization (ATRP) was utilized to grow the polymer chains on the magnetic mesoporous silica nanoparticles. The chemical surface modifications were confirmed using IR, TGA, SEM and TEM. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The functionalization process was achieved through the atom transfer radical polymerization (ATRP) technique, resulting in spherical nanoparticles with a magnetic core and an average size of approximately 30 nm. The researchers found that the adsorption capacity of the functionalized nanoparticles was unaffected by the pH range studied (pH = 3 to pH = 9), and the adsorption efficiency for both dyes was 100% [ 152 ]. These studies demonstrate that the functionalization of nanoparticles with positively charged polymers enhances the adsorption efficiency of anionic dyes by facilitating interactions with their negative charges.…”
Section: Adsorption Applicationsmentioning
confidence: 99%
“…The functionalization process was achieved through the atom transfer radical polymerization (ATRP) technique, resulting in spherical nanoparticles with a magnetic core and an average size of approximately 30 nm. The researchers found that the adsorption capacity of the functionalized nanoparticles was unaffected by the pH range studied (pH = 3 to pH = 9), and the adsorption efficiency for both dyes was 100% [ 152 ]. These studies demonstrate that the functionalization of nanoparticles with positively charged polymers enhances the adsorption efficiency of anionic dyes by facilitating interactions with their negative charges.…”
Section: Adsorption Applicationsmentioning
confidence: 99%
“…290 and 237 mg g –1 for chlorophenoxy herbicides and paracetamol, respectively. Beagan et al reported the preparation of magnetic MSNPs modified with (poly­(2-methacryloyloxy)­ethyl] trimethylammonium chloride solution) brushes as a nanomaterial to remove MO and bromothymol blue dyes from contaminated water . The synthesized nanomaterials showed a large maximum adsorption capacity, with 547 mg g –1 for MO and 344 mg g –1 for MB.…”
Section: Introductionmentioning
confidence: 99%
“…25 Our previous work affirms that the adsorption performance of MSNPs could be significantly improved after surface modification with polymer brushes via SI-ATRP. 26,27 Jing et al reported the preparation of lysine-attached poly(glycidyl methacrylate) (PGMA) brushes grafted to magnetic nanoparticles for the removal of lemon yellow (LY) and MB from wastewater. 28 Their results showed that the Lys− PGMA nanocomposite was an excellent nanoadsorbent for the selective removal of dyes from water, with adsorption capacities of 0.54 and 0.85 mmol g −1 for LY and MB, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Of notable concern are the dyes found in waste effluent, which can have serious consequences for a variety of living organisms. The pollution caused by dye products combines both danger to health and environmental unattractiveness [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%